ANALISIS PENDAPATAN DAN RANTAI PEMASARAN USAHATANI KEMIRI (Aleurites moluccana Willd) DI DESA BANGKA ARUS, KECAMATAN POCO RANAKA TIMUR, KABUPATEN MANGGARAI TIMUR - Nixon Rammang; Kamelia S. M. Risna; Paulus Un (Program Studi Kehutanan, Fakultas Pertanian, Universitas Nusa Cendana, 2019)
This study aims to analyze: 1) how the technical aspects of Candlenut cultivation; 2) how much income and profits of farmers; 3) how is the marketing chain of Candlenut. This research was conducted in Bangka Arus Village, Poco Ranaka Timur District, Manggarai Timur Regency. The survey method was conducted in December 2018 - January 2019. Data collected in the form of primary data and secondary data. Primary data was obtained through interviews with 210 farmers who were determined based on simple random sampling and secondary data obtained from the stakeholders. The data analysis used was descriptive analysis and analysis of farm income, as well as the R/C ratio. The results of research showed that: 1) the technical aspects of Candlenut farming (Aleurites moluccana Willd) in Bangka Arus Village, Poco Ranaka Timur District, Manggarai Timur Regency were sources of seeds, planting and spacing, maintenance, age of plants, other types of plants, soil types, and slope of land; 2) total costs incurred by 210 respondent farmers in Bangka Arus Village were Rp 77.850.000 with an average of Rp 370.714 per respondent farmer while the total receipt was Rp 753.006.000 with an average of Rp 3.485.743 per respondent farmer. The total income received by respondent farmers was Rp 675.156.000 with an average of Rp 3.215.028 per respondent farmer. Candlenut farming (Aleurites moluccana Willd) in Bangka Arus Village is feasible and profitable for farmers to cultivate with a revenue ratio with a total cost of 15,84; 3) there are four marketing chains of Candlenut in Bangka Arus Village, Poco Ranaka Timur District, Manggarai Timur Regency namely: I (farmers, village level collectors, district level collectors and wholesalers), II (farmers, village level collectors and wholesalers), III (farmers, district level collectors and wholesalers), IV (farmers and wholesalers).